Huge Congenital Segmental Dilatation of the Sigmoid Colon in a Neonate: A "Rarity to Meet" and a "Challenge to Treat" - Margarita Kaiser; Christoph Castellani; Georg Singer; Robert Marterer; Manfred Ratschek; Holger Till (Hindawi Limited, 2016)
Only ten cases of neonatal congenital segmental dilatation (CSD) of the colon have been described so far. We present a full-term female newborn with trisomy 21, ventricular septal defect, and gross abdominal distension. Plain abdominal radiographs revealed a huge cystic lesion occupying the left hemiabdomen. Upon laparotomy on day 4 a CSD of the distal sigmoid and proximal rectum was confirmed and resected. The proximal colon was exteriorized and the distal part closed as a Hartmann pouch. Histology confirmed a huge segmental dilatation of the sigmoid without dysganglionosis or pseudodiverticula, but normal intestinal architecture. After correction of the ventricular septal defect a low rectal end-to-end anastomosis could be performed at an age of 5 months. The postoperative course was uneventful. CSD of the sigmoid colon is extremely "rare to meet" and a "challenge to treat" in the newborn period, but clinical awareness of this entity prompts pediatric surgical success.